Ecological Study of Trees Diversity and Carbon Sequestration Potential of Ratanpur Forest, Dungarpur Division, Rajasthan - Purani, Kuldip; Patel, Jitendra S. (Indian Forester, 2025)
Ecological studies assess the biodiversity status of vegetation. Knowledge of ecological composition, tree species variety, and dominating ecosystem communities serves as a framework for biodiversity conservation management planning and implementation. This study focuses on characterizing the diversity and phytosociological attributes of tree species in surrounding the Ratanpur forest areas of the Dungarpur division of the Rajasthan state. The research employs a total of 15 stratified random sampling plots laid, and a total of 30 tree species belonging to 22 genera and 27 families have been recorded. The study revealed that the total density of tree species was 1090.13 individuals/ha. in the whole Ratanpur forest area. The estimated carbon sequestration of these tree species has been calculated using a non-destructive method. Among these 30 tree species, 90.31 tonnes of carbon were stored, with the maximum carbon storage found in Tectona grandis (Sag) (21.78 tonnes of carbon). This detailed understanding of the phytosociological characteristics of the tree species will enable better forest management, conservation efforts, and sustainable utilization of forest resources.